2010
DOI: 10.1029/2009jd013713
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened tropical circulations in past three decades inferred from water vapor transport

Abstract: [1] By relating the water vapor flow from both reanalysis data and satellite observations to the lower branches of the Hadley and Walker circulations, it was shown that the strength of both north-south and east-west tropical circulations has intensified since 1979. Consistent with the expected water vapor climatology under the strengthened north-south Hadley circulation, satellite observations of upper tropospheric humidity and total water vapor show that the subsidence region has become drier because of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
86
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 26 publications
10
86
1
Order By: Relevance
“…It is also plausible that temporary increases in the strength of the tropical circulation may yield larger precipitation responses than anticipated (e.g., Wentz et al 2007) relative to secular trends (e.g., Semenov and Bengtsson 2002). There are also some limited observationally based analyses which suggest increases in tropical circulations (e.g., Sohn and Park 2010;Zahn and Allan 2011) although these changes may be sensitive to the assimilation of erroneous temperature lapse rate observations in the reanalyses employed . It is not currently clear what mechanisms drive decadal variability, nor whether the observing systems are of sufficient stability to capture such changes accurately (Trenberth 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is also plausible that temporary increases in the strength of the tropical circulation may yield larger precipitation responses than anticipated (e.g., Wentz et al 2007) relative to secular trends (e.g., Semenov and Bengtsson 2002). There are also some limited observationally based analyses which suggest increases in tropical circulations (e.g., Sohn and Park 2010;Zahn and Allan 2011) although these changes may be sensitive to the assimilation of erroneous temperature lapse rate observations in the reanalyses employed . It is not currently clear what mechanisms drive decadal variability, nor whether the observing systems are of sufficient stability to capture such changes accurately (Trenberth 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that HIRS upper tropospheric humidity closely tracks ENSO evolutions (Bates et al, 1996;McCarthy andToumi, 2004, andBates, 2011). HIRS channel 12 observations provided valuable information for examining the strong interaction between tropical and midlatitude planetary waves ) and changes in tropical circulations in the past three decades (Sohn and Park, 2010). A long-term HIRS channel 12 dataset was used in the evaluation of climate model simulations (Iacono et al, 2003).…”
Section: Shi Et Al: Hirs Channel 12 Brightness Temperature Datasetmentioning
confidence: 99%
“…The weakening trend is caused by the anthropogenic climate change and can be understood through energy and mass balance of the ascending branch in the circulation (Held and Soden 2006;Vecchi et al 2006). On the contrary, several studies in recent years explained differently (Sohn and Park 2010;Meng et al 2012). In particular, Sohn and Park (2010) analyzed the water vapor transport and described strengthening of tropical circulation during the past three decades.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, several studies in recent years explained differently (Sohn and Park 2010;Meng et al 2012). In particular, Sohn and Park (2010) analyzed the water vapor transport and described strengthening of tropical circulation during the past three decades. Dong and Lu (2013) showed the recent enhancement of Walker circulation since the late 1990s.…”
Section: Introductionmentioning
confidence: 99%